Analysis of the structural models of competencies in project management - Lukianov, Dmytro; Kolesnikov, Olexii; Dmitrenko, Katerina; Gogunskii, Viktor (Technology audit and production reserves, 2017)
The analysis of structural models that reflect the topology of project management processes using directed graphs is performed. It is shown that the essence of the analysis of directed graphs is connected with the determination of closed cycles. To solve the problem of analysis of structural objects, it is proposed to use the method of analytical definition of cycles in complex systems describing the set of competences in the field of project management. At the same time, it is necessary to take into account the industry component of the field of knowledge. The requirements for the evaluation of competencies, as well as for the system of training professionals in the field of project management, it would be very logical to harmonize with the specifics of the industry. At the same time, universal models do not offer acceptable solutions. Therefore, in this research, it is proposed to resolve this contradiction on the basis of an analysis of the system of competencies as directed graph. The possibility of structural analysis of directed graphs due to specific properties of adjacency and reachability matrices is proved, which makes it possible to automate the structural analysis of control schemes based on the competence approach. Aspects of knowledge management are traditionally considered as the main component of project management and as an object of study in the professional training of project managers. The second direction is, strangely enough, the least studied, although the training and trainings allow to resolve the contradictions of the project management. Existing approaches to knowledge management in the field of professional project management do not always provide an effective formation of the education trajectory due to the lack of models, methods and means of analyzing the relation of competencies. The mutual relations of competences form the core of knowledge that forms the basis of fundamentally new provisions in the formation of the content of academic disciplines. The theoretical provisions of this study can be applied in the practice of professional project management and advanced training to form the trajectory of career development of personnel.